Invasive Alien Plant Species for Use in Paper and Packaging Materials - Urška Vrabič-Brodnjak; Klemen Možina (Fibers, 2022)
Invasive plant species can impede the establishment and growth of native plants and affect several ecosystem properties. These properties include soil cover, nutrient cycling, fire regimes, and hydrology. Controlling invasive plants is therefore a necessary, but usually expensive, step in restoring an ecosystem. The sustainability of materials with an emphasis on the use of local resources plays an important role in the circular economy. The use of alternative fibers from invasive plants promotes local production in smaller paper mills that offer the protection of local species and the reduction of waste and invasive plants. A synthesis of the literature is needed to understand the various impacts of invasive plants and their practical control in the context of papermaking applications and to identify associated knowledge gaps. To improve our understanding of the practical application of invasive species in the paper industry, we reviewed the existing literature on invasive plant species in the area of fiber production, printability, coating solution production, dyes, and extracts, and collected information on the major invasive plant species in Europe and the methods used for various applications.